Effect on Video Conference’s Education in Mandangin’s Community Health Center’s Healthcare Knowledge about Acute Diarrhea in Children - Alpha Fardah Athiyyah; Andy Darma; Dwiyanti Puspitasari; Khadijah Rizky Sumitro; Ni Nyoman Metriani Nesa; Steven Christian Susianto; Muhammad Faizi; Reza Gunadi Ranuh; Subijanto Marto Sudarmo (Asian Journal of Health Research, 2023)
Introduction: The involvement and ability of health workers in Mandangin Island in early managing acute diarrhea in children to reduce infant mortality due to diarrhea are very important. This study aimed to determine the effect of community development Faculty of Medicine Universitas Airlangga - Dr. Soetomo General Academic Hospital Surabaya in a seminar on Early Management of Acute Diarrhea in Children using video conference to educate health care workers (HCWs) at the Mandangin Community Health Center. Material and Methods: This cross-sectional study was designed on 20 HCWs at the Mandangin community health center. Subjects were evaluated for demographic data (gender, age, occupation, last education), and the knowledge was assessed using a pre-test before the seminar was given. We used questionnaire about acute diarrhea containing 10 questions with maximum score 100. The seminar was given through video conferences with form classical lecturer and a case study on acute diarrhea, and subjects attended the seminar in Community Health Center’s Hall. We assessed knowledge after the seminar using the same questionnaire with randomization in question and answer and compared the pre-and post-test using the Wilcoxon Rank sum test. Results: Most of the subjects were midwifery, with a mean age of 32.4 ± 5.75 years old, 45% with D-3 last education and 80% were female. There was a significant difference between pre-and post-test in acute diarrhea in children (47.89±20.7 vs 64.74±22.94) (p=0.008). Conclusion: Video conference education effectively increased health care workers' knowledge about acute diarrhea in children